Facile ligand transformation from bridging thio to terminal chloromethanethiolato. Bridge opening of [Pt(μ-S)(dppf)]2 by dichloromethane to give Pt(SCH2Cl)2(dppf) [dppf Fe(C5H4PPh2)2] - Meisheng, Z. (2014)
Journal of Organometallic Chemistry